To Be or Not To Be: Twitter Presence among Turkish Diplomats - H. Mehmetcik; E. Salihi (Vestnik MGIMO-Universiteta)
The article studies Turkey’s twiplomacy how Turkish diplomats use Twitter in performing their diplomatic outreach and public diplomacy. The literature review shows that there is a lack of a comprehensive large N study of Turkey’s twiplomacy. The article fills in this gap by collecting and analyzing data set of Twitter posts by 76 diplomats from 2010 to 2020. It helps understand how and to what extent Turkish diplomats maintain their presence on Twitter. We achieve this goal using two groups of methods. Firstly, we derive descriptive statistics for several user metrics including raw numbers of tweets per user and per date as well as retweet, reply, and like counts per user. Secondly, we analyze content of tweets through calculation of their sentiment scores.The main findings indicate that the Twitter presence of Turkish diplomats is relatively limited and reliant on a few prominent figures. Though Turkish diplomats are selected from well-educated individuals who can make the greatest use of available opportunities provided by social media, relatively few of them are active on Twitter. Another significant conclusion is that Turkey’s twiplomacy is inconsistent and driven by individuals rather than a part of a wider strategy or framework. Online activities of different state institutions are not synchronized for efficient use of social media and so-called twiplomacy. Finally, according to the results of the content analysis, Turkish diplomats usually employ positive language in their tweets, as seen by the most frequently used terms, related emotions, and sentiment scores. It confirms the idea that Turkish diplomats tend to promote messages demonstrating Turkey's endorsement of international cooperation.